31. RESULTS OF DETERMINING THE CAUSE OF LOWER RESPIRATORY TRACT INFECTIONS USING FILM ARRAY IN INPATIENTS AT THE NATIONAL HOSPITAL FOR TROPICAL DISEASES FROM 2020 TO 2022 (Vietnam Journal of Community Medicine, 2024)
Objectives: Characterization of the etiology of microorganisms causing lower respiratory tract diseases using automated multiplex PCR (Film Array) in patients with lower respiratory tract infections treated at the National Hospital for Tropical Diseases from 2020 to 2022.Methods: Retrospective study of 197 patients with lower respiratory tract infections who were prescribed Film Array and cultured at the National Hospital for Tropical Diseases from 2020 to 2022.Results: The Film Array positivity rate was 67%, and the culture rate was 33%. In which, the main typical bacteria are A. baumanii complex with the largest proportion of 22.95%, K. pneumonia 18.49%, S. aureus 7.53%, atypical bacteria L. pneumophila 0.34%, Coronavirus virus 3.55%, Human Rhinovirus 1.52%, Influenza A 0.51%; 9 typical virus-bacteria co-infected specimens. 290 antibiotic resistance gens were detected, CTX-M gen had the highest proportion of 25.9%, NDM, KPC, OXA-48 like gens had similar proportions, mecA/ and MREJ, VIM gens had the lowest proportion of 2.1%. Culture did not detect atypical bacteria, viruses and drug resistance gens.Conclusion: Film Array has a positive rate 2 times higher than culture in the study, detecting both atypical bacteria, viruses, virus-bacterial co-infection and drug resistance gens.
Keywords: Film Array; lower respiratory tract infections